Cultural centered web design for Kelantan tourism website enhancement / Syakirah Suhaimi - Suhaimi, Syakirah (2019)
Web tourism is very important in the tourism industry because it can help the particular country to promote their own culture and uniqueness especially for every regional tourism. Kelantan state also takes part of promoting their own culture to their potential tourists that comes from various places such as local and international. Therefore, for this project the latest web technologies such as interactive multimedia elements are really helpful to enhance the current Kelantan tourism website. By adding the cultural elements such as material culture into this project makes the website looks interesting and attract the potential tourists to visit the website. Nowadays, there are a lot of tourism websites have implemented the cultural website. The purpose of this project is to propose the Cultural Centered Web Design for Kelantan Tourism Website Enhancement. Hofstede cultural model becomes a guideline to design this project. This model consists of six dimensions which are Power Distance Index (PDI), Individualism vs Collectivism (IDV), Uncertainty Avoidance (UAI), Maculinity vs Feminity (MAS), Long Term Orientation vs Short Term Orientation (LTO) and Indulgence vs Restraint (IND). The current website are still lacking in terms of cultural information and also web design. The scope of this project is for the target users are the local and foreign tourist. Next, the modules only cover the cultural information which are interesting places to visit, local foods and traditional games and performances, 360 videos, searching box according to categories and also sharing information through the social media such as Facebook and Instagram. Malay language becomes one of the limitation in this project because for now it only focus on the potential tourists that can understand Malay language and also for the tourists that are interested to visit Kelantan such as local and foreign tourists. The potential foreign tourists can come from the Indonesia,Singapore and Brunei. The other limitation is the internet connection is required to access this project because without them it is hardly for the tourists to retrieve the information about Kelantan on the website. The Web Development Life Cycle (WDLC) is the methodology used to develop the Cultural Centered Web Design for Kelantan Tourism Website. This WDLC consists of several phases such as planning, analysis, design and development, testing and implementation and maintenance. This project development is only until the testing phase. For the future work, this project can be enhanced by translate the information into various languages such as English, French and etc.